Fat bodies, diet culture, and human flourishing: How did we get it so wrong? - Bowden, Jennifer (Dialog, 2024)
Contemporary diet culture is detrimental to many Western men and women, though women are disproportionately impacted. This results in poor body image, low self-esteem, and unhealthy lifestyles. Christian discourse is not immune to the influence of diet culture, with many popular Christian pastors and authors adopting this paradigm and seeking to align it with a Christian worldview. When an understanding of a human being as an anthropological duality is brought to bear on the issue of diet culture, a more consistently Christian anthropology can resource a healthier view of the embodied self and provide resources for a robust Christian response to diet culture.